Analisis Kepemimpinan Kepala Sekolah dalam Meningkatkan Efektivitas Manajemen Pendidikan di Sekolah Dasar - Wesi Salsabela (Institut Agama Hindu Negeri Tampung Penyang Palangkaraya, 2026)
This study was motivated by the importance of school principals’ leadership in managing elementary education more effectively, particularly in schools with limited resources. The objective of this study is to analyze the leadership of the school principal in improving the effectiveness of educational management at SD Negeri 76/I Sungai Buluh, Batanghari Regency, Jambi Province. The method used in this study is a descriptive qualitative approach with data collection techniques through direct observation, semi-structured interviews, and documentation. The research subjects consisted of 23 informants, including the principal, teachers, and students. These informants comprised 1 principal as the main informant, 2 teachers as supporting informants, and 20 fifth-grade students as additional informants. The findings indicate that the school principal employs a democratic-participatory leadership style, reflected in collaborative planning, competency-based organization, implementation through deliberation and persuasive communication, and monitoring via routine classroom supervision. Limited facilities and operational funds constitute the primary obstacles. Overall, educational management at this school can be categorized as fairly effective, with the principal’s leadership serving as the primary support for that effectiveness.